Investigating the impact of caste, class, and gender on student attitudes to English in India - Ramasubramanian, A (2022)
Prior research has noted that different social variables can predict the direction and magnitude of language attitudes, across contexts. However, to the best of our knowledge, no studies have investigated whether one’s position in the the South Asian caste system affects their attitudes towards different languages. To fill this gap, this study uses thematic analysis to explain attitudes towards English in 10 school students aged 13-14 at a public school in Mumbai, India. Data was gathered through semi-structured interviews and field notes. The participants were found to come from different castes, each with a history of struggle for power within the caste hierarchy. Results indicate that caste location does significantly influence attitudes towards English; however, this effect is likely mediated by the language ideologies with which the students have been in contact.